Metamorfoses na cidade: tensões e contradições na produção e apropriação do espaço urbano em Foz do Iguaçu - Ribeiro, Danilo George (2015)
This research work aims to investigate the social struggles in the process of urban space production in Foz do Iguaçu PR. The problematization that guided this work is concentrated on the process of urban transformation in the city, acknowledged as one of the main tourist destinations of Brazil. The grounding perspective is that urban space is a socially produced construct, whose concept enabled this study to be comprised within the realms of historical materialism and its relationship with social classes. In this respect, this research channeled efforts to explore the contradictions that suffused the process of appropriation of the urban space due to the development of tourism, as well as the conflict with local communities established in regions claimed to have economical and tourist interests in municipality. Therefore, we sought to identify the multiple historical subjects involved in this process by means of analyzing historical, written and oral sources. This procedure made room for revealing aspects of the material and symbolic construction of the city, paving the way for understanding the relationship between the social classes with the production and appropriation of the urban space.